IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA YAYASAN PERGURUAN NURUL IMAN KEC. TANJUNG MORAWA, KAB. DELI SERDANG - Geniza Aidilla Syuaira; Neliwati; Laila Qodri; Muhammad Syah Mahathir (Jurnal Genta Mulia, 2024)
The 2013 curriculum is the result of the government's follow-up in refining the previous curriculum. The 2013 curriculum is based on thinking about future challenges, namely the challenges of the 21st century which is marked by a century of science, knowledge-based society and future competencies. Before the 2013 curriculum is implemented, it must have planning, implementation and evaluation aimed at seeing whether the implementation of the curriculum has been carried out properly or not. The research conducted by the author using qualitative research was carried out in natural conditions with descriptive research results emphasizing words not numbers, in addition to the type of research the author carried out data collection techniques using interviews, observations, and documentation analysis The results of the research obtained showed that the implementation of the 2013 Curriculum was carried out by teachers of Islamic Religious Education subjects at SMA Yayasan Perguruan Nurul Iman Tanjung Morawa It has been going well, although there are some inhibiting factors that affect the learning process. This can be seen in the planning, implementation and evaluation stages of learning in accordance with the rules of implementation of the 2013 curriculum. Although there are some factors that hinder the evaluation process, there are some things that must be improved.